Application of Saving Matrix Approach for Minimize Distribution Cost and Route Optimization: A Literature Review - Noviwiyocha, Riza; Matondang, Abdul Rahim; Hidayati, Juliza (TALENTA Publisher, 2023)
The objective of this research is to review the application of the savings method, to obtain optimal distribution routes. Data collection and observation of this literature review were obtained from scientific publications that were published from 2014 to 2022. The main purpose of this review study is to investigate, discuss, analyze, and the existence of various types of distribution routes problems and their solving methods. The application of the research methodology resulted in 20 articles, which aimed to identify the saving algorithms used, over the last decade. As a result, these articles were reviewed and selected using a table for further analysis This paper also presents the results of a quantitative and qualitative literature review and discusses scientific publications that have had a significant impact on logistics companies. Finally, findings show that using the savings matrix method, it is proven that this method generates a better route distribution.